Pengembangan Lembar Kerja Peserta Didik (LKPD) Media Blended Learning Bermuatan Karakter Baik dan Kuat (Baku) - Hasanah, Salati Asma; Muhyani; Albahar, Rheenda K. (UNIB Press, 2023)
The purpose of this study is to develop LKPD Media Blended Learning contains Good and Strong characters. Good characters indicated by Sincere, Honest, Trusted, Humble